THE EFFECTIVENESS OF USING ANAGRAM GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Fadhilatul Lailiyah; Sayid Ma’rifatulloh (Program Studi Pendidikan Bahasa Inggris, 2024)
The objective of this research is to find out whether or not the use of anagram game effective to improve the students’ vocabulary mastery. The researcher conducted a pre-experimental group design. The population of this research is the seventh-grade students of SMPN 1 Diwek Jombang in academic year 2023-2024. The total number of the first-class is 256 students. The sample in this study was class VII-A SMPN 1 Diwek Jombang, totaling 32 students. Based on the data normality test that has been carried out by the researcher, it shows that sig. 2-tailed in pre-test is 0.200 and post-test is 0.100 meaning that the data is normally distributed, the it will be continued with a simple paired t-test. Based on the testing of hypothesis terms, if the score of t is sig. <0.05, H1 is accepted and H0 is rejected. On the simple paired t-test calculation, the data shows sig. (2-tail) 0.000. the data is smaller than 0.05, meaning that H0 is rejected and H1 is accepted.